Implementation of Human Rights as a Prevention of Discrimination Against Aborigines by European Nations (1967-2022) - Made Darme; Kurniawati (Criksetra: Jurnal Pendidikan Sejarah, 2024)
Abstract: The existence of Aborigines experienced a bitter life after the arrival of Europeans in Australia. The various policies that were formed were completely controlled by white people, regardless of indigenous Australians. The purpose of this research is to find out and analyze the implementation of human rights in Australia in protecting the Aborigines from being treated by Europeans in 1967-2022. The method used in this study is the historical method, which includes heuristics, criticism, interpretation, and historiography. The results of the analysis obtained the lack of attention from the Australian government towards the Aborigines as the original inhabitants who occupy the first territory of Australia. This can be seen from acts of discrimination such as race, sexuality, age, disability, and human rights which are of concern to indigenous Australians. To fight for rights and equality between white people and indigenous people (Aborogins) a referendum was formed in 1967. This effort was implemented as a form of dismissing policies that were entirely only important for Europeans. The fact is that the enactment of the policies set is still unable to protect Indigenous Australians, but the implementation of this constitution can reduce the occurrence of discriminatory acts committed by Europeans. Abstrak: Keberadaan suku Aborigin mengalami kehidupan yang pahit setelah kedatangan bangsa Eropa di Australia. Berbagai kebijakan yang dibentuk sepenuhnya dikuasai oleh orang-orang berkulit putih, tanpa menghiraukan penduduk asli Australia. Tujuan penelitian ini untuk mengetahui dan menganalisis pelaksanaan Hak Asasi Manusia yang ada di Australia dalam melindungi suku Aborigin dari perlakuan bangsa Eropa tahun 1967-2022. Metode yang digunakan dalam penelitian ini adalah metode sejarah, yang meliputi heuristik, kritik, interpretasi, dan historiografi. Hasil analisis diperoleh kurangnya perhatian pemerintah Australia terhadap suku Aborigin sebagai penduduk asli yang menempati pertama wilayah Australia. Hal ini terlihat adanya tindakan diskriminasi seperti ras, seksual, usia, disabilitas, dan hak asasi manusia yang memprihatikan terjadi pada warga pribumi Australia. Untuk memperjuangkan hak dan kesetaraan antara bangsa kulit putih dengan penduduk asli (Aborogin) dibentuklah referendum tahun 1967. Upaya ini diberlakukan sebagai bentuk pemberhentian kebijakan yang sepenuhnya hanya dipentingkan bagi bangsa Eropa. Faktanya pemberlakuan kebijakan yang ditetapkan masih belum mampu melindungi warga pribumi Australia, namun dengan adanya penerapan konstitusi ini mampu mengurangi terjadinya tindakan diskriminasi yang dilakukan oleh bangsa Eropa.